Calidad del servicio de la Microempresa Santistevan de la ciudad de Babahoyo - Morán Yépez, Manuel Sebastián (2021)
Customer service has become one of the effective strategies to attract and retain customers, therefore, this study proposes to analyze the factors that affect the quality of the service of the Santistevan technical service microenterprise through the application of descriptive method, analytical and bibliographic in addition to the research line "Financial, administrative, tax, audit and control management" and with the sub-line "Public and private companies". That has allowed the identification of problems such as: the owner-administrator is unaware of the importance of the quality of the service, insufficient processes that affect the fulfillment of the customer service stages (dismissal- assessment of customer satisfaction), the staff lacks of knowledge in the customer service area, lack of tools and adequate infrastructure (space), deficient protocols, policies and processes, long waiting time, lack of social profile (networks) to generate immediate responses to customers regarding The products and services it offers do not measure the degree of customer satisfaction, the absence of a complaint and suggestion box, high customer turnover and the lack of a strategic customer service plan. Everything raised during the development and generates the description, analysis and contrast of the facts obtained from various authors of texts that refer to the quality of customer service and has an impact on the corporate image of the microenterprise.